2011
DOI: 10.1186/1471-2458-11-217
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of timely initiation of breastfeeding among mothers in Goba Woreda, South East Ethiopia: A cross sectional study

Abstract: BackgroundAlthough breastfeeding is universal in Ethiopia, ranges of regional differences in timely initiation of breastfeeding have been documented. Initiation of breastfeeding is highly bound to cultural factors that may either enhance or inhibit the optimal practices. The government of Ethiopia developed National Infant and Young Child Feeding Guideline in 2004 and behavior change communications on breast feeding have been going on since then. However, there is a little information on the practice of timely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

43
146
11
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(208 citation statements)
references
References 9 publications
43
146
11
2
Order By: Relevance
“…The prevalence of timely initiation of breast feeding observed in the study area is 41.6%.This is lower than compared to finding of EDHS,2011 which was 51% [9], finding of a research done in Nepal 2010 (14), which was 46.7 % , finding of a research done by JSI /L10K base line house hold survey in 2009(13) which was 45% and finding of a research done Goba Woreda, South East Ethiopia, 2011 [15], which was 52.4% but higher than EDHS 2011 Amhara region, which was 38% and also higher than finding of research done in Tanzania, December 2010 which was (18%) and higher than Jimma Arjo Woreda, Southwest Ethiopia, 2012 which was 37% [9][14] [16].…”
Section: Discussioncontrasting
confidence: 49%
“…The prevalence of timely initiation of breast feeding observed in the study area is 41.6%.This is lower than compared to finding of EDHS,2011 which was 51% [9], finding of a research done in Nepal 2010 (14), which was 46.7 % , finding of a research done by JSI /L10K base line house hold survey in 2009(13) which was 45% and finding of a research done Goba Woreda, South East Ethiopia, 2011 [15], which was 52.4% but higher than EDHS 2011 Amhara region, which was 38% and also higher than finding of research done in Tanzania, December 2010 which was (18%) and higher than Jimma Arjo Woreda, Southwest Ethiopia, 2012 which was 37% [9][14] [16].…”
Section: Discussioncontrasting
confidence: 49%
“…The orientation on breastfeeding by health professionals soon after birth increased the chance of women to breastfeed in the first hour of life 17 . Boccolini et al 20 found that mothers have limited or no power to make decisions about breastfeeding their children in the first hour of life, and shall be subject to the practices and actions of the professionals involved in the delivery, as well as to the institutional procedures in place in maternity wards.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has indicated that the practices of health professionals 8,[13][14][15][16][17][18] , as well as the organization and management of health services, are essential to the initiation of breastfeeding immediately after childbirth 12 . Mothers who got the prenatal care 13 , who were counseled during prenatal about breastfeeding 18 and who received postpartum assistance from health professionals for breastfeeding were more likely to breastfeed their children in the first hour 16,17 . With regard to health services, allowing companion in childbirth, having deliveries paid by the Unified Health System (SUS) and in hospitals that received the title of Child Friendly Hospital Initiative (IHAC) 12 were appointed as stimulating factor for the breastfeeding within one hour of birth.…”
Section: Palavrasmentioning
confidence: 99%
“…This may delay initiation among Indian women. Recently, a study in Ethiopia found that 35% of the women in their study discarded the colostrum due to belief it was bad for the child [41].…”
Section: Discussionmentioning
confidence: 99%